2011
DOI: 10.1002/jsfa.4667
|View full text |Cite
|
Sign up to set email alerts
|

Using ITS2 PCR‐RFLP to generate molecular markers for authentication of Sophora flavescens Ait.

Abstract: The present study demonstrates the usefulness of ITS2 PCR-RFLP coupled with pre-selected restriction enzymes for practical and accurate authentication of S. flavescens Ait. The technique is also suitable for analysing S. flavescens Ait. mixed with other adulterants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The regions of ITS 1 and ITS 2 are commonly used as character sources to determine the phylogenetic relationship. Amplification of target band on PCR product the region of ITS-1 and ITS-2 rDNA on more than 500 base pair (Baldwin et al, 1995;Baldwin & Markos, 1998;Lin et al, 2007Lin et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…The regions of ITS 1 and ITS 2 are commonly used as character sources to determine the phylogenetic relationship. Amplification of target band on PCR product the region of ITS-1 and ITS-2 rDNA on more than 500 base pair (Baldwin et al, 1995;Baldwin & Markos, 1998;Lin et al, 2007Lin et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…These results are not surprising, because the molecular assessments on internal transcribed spacer sequence showed that the tested S. flavescens populations have extremely low genetic variability (Lin et al, 2012). Since the karyological characteristics for the tested populations were similar, therefore, the karyotype data were presented as the means of the tested four populations (Table 1).…”
Section: Resultsmentioning
confidence: 86%
“…The advantages of the ITS regions made them a preferred choice in the past, as the ITS sequences were used as genetic markers for various species (Gao et al 2010;Sun et al 2011;Lin et al 2012;Ganopoulos et al 2012;Liu et al 2012). Slanc et al (2006) used ITS for the identification of four herbal drugs in tea mixtures.…”
Section: Resultsmentioning
confidence: 99%